Respuesta :
If you would like to solve a set of equations, you can do this using the following steps:
equation a: y = 15 - 2z /*(-2)
equation b: 2y = 3 - 4z
__________________
-2y = (-2) * (15 - 2z)
-2y = -30 + 4z
2y = 3 - 4z
The mistake was made at step 2: −2y = 15 − 2z [equation a in step 1 is simplified.]. The correct simplification would be -2y = -30 + 4z.
equation a: y = 15 - 2z /*(-2)
equation b: 2y = 3 - 4z
__________________
-2y = (-2) * (15 - 2z)
-2y = -30 + 4z
2y = 3 - 4z
The mistake was made at step 2: −2y = 15 − 2z [equation a in step 1 is simplified.]. The correct simplification would be -2y = -30 + 4z.
The step the student makes the error is in step 1 . The correct answer when you multiply equation(i) by -2 is -2y = -30 + 4z
How to find the variables in a system of equation?
y = 15 − 2z
2y = 3 − 4z
The mistake was made in step 1. let's multiply equation(i) by -2 to see the final value.
-2(y) = -2(15 - 2z)
open the bracket
-2y = -30 + 4z
The multiplication of -2 by the first equation result to -2y = -30 + 4z
learn more on system of equation here: brainly.com/question/19549073
#SPJ5